Construyendo posibilidades: intervención psicosocial en la escuela - Gastañaga Moreno, José Luis (Cuadernos de Trabajo Social, 2007)
This article discusses some professional practices carried out by the social worker in the school environment; the reflections are inspired by and are based on a set of theoretical contributions that have their basis in the systemic model and social constructivism. It deals with a self-reflection exercise, how that exercise is sustained, paying attention to the child’s context (family and school), an egalitarian and reciprocal linked modality —social worker-family-teachers, in which language as a builder of reality is the framework that provides meaning to the reflective practices that are proposed. Finally, it is argued that inclusive and collaborative practices are an axis for critical work in schools.